Resistência de união de um sistema adesivo de condicionamento total com diferentes viscosidades à dentina tratada com Laser de ER:YAG - Lira, Renato Queiroz Nogueira (2013)
Dental cavities prepared with Er:YAG laser may result in greater conservation of sound tissue, further opening of dentinal tubules without the presence of smear layer, few microorganisms in the cavity, and lower pain sensitivity during operative procedure. Whereas laser irradiation may decrease the bond strength of resin materials to dentin, this study examined the effect of viscosity of a two-step total-etch adhesive system on the bonding to dentin irradiated with Er:YAG laser. The prepared dentin was tested in 2 types of surface preparation (diamond tip and Er:YAG laser) and the viscosity of the adhesive at 3 different dilutions (Adper™ Single Bond 2 [SB], SB+10% e SB+20% de ethanol). Sixty human third molars were sectioned and polished, exposing dentin occlusal surfaces. SB adhesive system was used to prepare formulations with different viscosities. The dentin surfaces were acid etched and the adhesives were applied according to the manufacturer's instructions. Composite resin buildups (Filtek™ Z250 XT) of 5 mm were made. Prepared teeth were stored in distilled water (37oC) for 24 h. Specimens were sectioned into sticks (1 mm² of cross sectional area), which were submitted to microtensile test. Physical-mechanical properties, such as contact angle, evaporation rate, degree of conversion, sorption/solubility of water and viscosity of the adhesives were defined. All results were compared with Two-way ANOVA and Tukey multiple comparison test (α=0.05). There was no statistical difference between the values of microtensile for all groups. The viscosity levels did not affect the bond strength of dentin treated either with Er:YAG laser or diamond bur.